Topical drugs usage and patient compliance on topical drugs in Polyclinic Pharmacy, Hospital Sultanah Aminah, JB - Taib, Hanisah; Mohd Amin, Nurul Syazwani; Rafie, Marziana; Ahmad, Nasrul Hadi (2008)
Purpose : 1) to determine 5 highest topical drugs being used in Polyclinic Pharmacy, Hospital Sultanah Aminah within 6 months 2) to evaluate patient compliance on topical drugs usage and their understanding on instruction given by pharmacist Methods : 1) Sample of this study were patients who already using topical drugs from Polyclinic Pharmacy within period of study. 2) A survey form that consists of multiple choice questions and 5 - point categorical rating scales were distributed to patients. Results : 1) 5 topical drugs that frequently used were Aquaes cream, Bethamethasone cream/ointment, Fusicort, Sebitar and Momethasone furoate. 2) 200 respondent were involved in this study, 75 % of them were compliance while other 15 % were not compliance. Through this survey, 77 % of respondent were understands the instruction of using topical drugs while other 13 % were not understands. Conclusion : 1) The stocks of these 5 highest topical drugs : Aquaes cream, Bethamethasone cream/ointment, Fusicort, Momethasone Furoate and Sebitar shampoo should be monitored. 2) Majority of patients at Polyclinic Pharmacy were compliance and understands the instruction of using their topical drugs given by pharmacist.